A socio-economic study on village sheep and goat production system in the humid tropical zone of Southwest Nigeria - Sempeho, G.J.M. (1985)
Although the indigenous West African Dwarf breeds of sheep and goats (the Djallonke) are known to be trypanotolerant and the most predominant livestock species in the highly populated and testes-infested humid zone, they have not received the desired recognition as far as government policy and research efforts are concerned. This study, which was carried out as an integral part of the multi-disciplinary research concept of the International Livestock Center for Africa (ILCA) in southwest Nigeria, was based on the general hypothesis the farmers’ incomes and the overall meat supply will increase in the increasingly high demand of improved forms of livestock management, particularly improved health control measures incorporated with improved nutritional base. The study covers general agricultural and socio-economic aspects and examines the present structure and constraining factors to improved sheep and goat production within the existing farming systems typical for the humid zone of west Africa.